Comparative Quality Evaluation of Frozen Stored Litopenaeus vannamei Reared in Inland Saline Water and Brackish Water - Javith S, Mohammed Akram; Xavier, K.A. Martin; Nayak, Binaya Bhusan; Kumar H, Sanath; Balange, Amjad Khansaheb (Fishery Technology, 2023)
The present study was aimed to investigate the quality changes of Pacific white shrimp (Litopenaeus vannamei) reared in inland saline water (ISRV) with those reared in natural brackish water (BWRV) during frozen storage. Freshly harvested L. vannamei shrimp cultured in inland saline water and brackish water were collected and biochemical, microbial and sensory quality parameters were evaluated for 5 months during frozen storage with sampling interval of 30 days. From the biochemical quality analysis, it was observed that pH, TVB-N and TMA values increased in both BWRV and ISRV samples. The total viable count of both the samples decreased initially and in the later stage it increased and reached the level of 4.52 log CFU/g in BWRV sample and 4.48 log CFU/g in ISRV sample. However, these values were within the acceptable limit of TVC. Sensory scores were within the acceptable limit for BWRV and ISRV samples during frozen storage of 5 months.